Feeding practices among mothers in Lopez, Quezon - Mondragon, Loreta Tabernilla
This study was inspired by the thrust of the Department of Health's projects to promote breastfeeding practices among mothers. Breastfeeding as a preventive measure, is a prime source of nutrition for the baby especially during the first year of the child's life.The research carried the following objectives:1. To identify the type of infant feeding practices in the identified three barangays of Lopez, Quezon.2. To determine the factors that underline their type of infant feeding;3. To identify the mothers'cognitive level on breastfeeding and infant care practices; and4. To determine a relationship between the factors that influence their knowledge about infant feeding and consequential infant feeding practice.Based on these objectives, the study attempted to answer the following research problems:1. What are the feeding practices among mothers in the three identified barangays in Lopez, Quezon?2. What are the factors that influence the type of feeding practices?3. What is the mothers' cognitive level regarding breastfeeding?4. Is there a significant relationship between the factors that influence the knowledge about infant feeding and the consequential infant feeding practice? The conceptual framework of this paper banks its stronghold on what taggart (1976) Bernard (1977) Clavano (1989) and others emphasize that infant feeding is most beneficial in the psychological, physiological and emotional dimensions when the baby is given the mother's milk. Breastmilk is a prime nutrition par excellence above all other formulae of manufactured milk. But mothers must be adherent to this concept. The formulation of the hypothesis was based on this conceptual framework.The research design made use of the qualitative exploratory survey with home visits interview. Tools were constructed to elicit the mothers' knowledge, attitudes and practices on infant feeding. Their opinions, ideas, beliefs and practices were analyzed upon the light of the conceptual framework.The major findings of this investigation are summarized as follows:The desirability of breastfeeding practice was recognized by 78.82(N=134) of the mother respondents while 21.18(N=36) opted for bottlefeeding. The knowledge and positive attitude of those mothers recognizing the desirability of breastfeeding favor this feeding practice. They know that breastmilk have nutritional and protective value aside from it being economical, safe, and ready at all times. On the other hand, the mothers who practice bottlefeeding considered this as a feasible option because theya re to work away from home; they have extra earnings and they can afford commercial milk. Mothers who were not working claim that their practice of bottlefeeding was due to unsuccessful lactation. They lack knowledge on ways to enhance milk production which contributed to their failure to lactate. Oftentimes, these mothers do not really lack milk, but they have this negative attitude towards breastfeeding or lack of enthusiasm that they opt to practice bottlefeeding.One good reason from breastfeeding is the value of this feeding practice as a family planning method. This was attested by 73.53(N=125) of the respondents who experienced delayed menstruation. However, 18.82(N=37) of the respondents do not subscribe to this belief because they got pregnant just the s